Pengaruh Pemberian Pupuk NPK terhadap Pertumbuhan dan Hasil Tanaman Kangkung Darat (Ipomoea reptans poir.) secara Terapung - Ammar, Muhammad; Susilawati, Susilawati; Irmawati, Irmawati; Harun, M Umar; Achadi, Teguh; Sodikin, Erizal; Wulandari, Safitri Safari (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2022)
Ammar M, Susilawati S, Irmawati I, Harun MU, Achadi T, Sodikin E, Wulandari SS. 2022. The application of NPK fertilizer on growth and yields of kale (Ipomoea reptans poir.) in floating system. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 628-634. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).South Sumatra Province is a province with great swampland potential. One of the uses of lebak swamp land is by floating cultivation. Floating cultivation in this study used a raft made of 10 bamboos with a size of 2x1 M. This study aimed to determine the effect of npk fertilizer application on the growth and yield of land kale plants in a floating manner. This research was carried out Embung on the campus of Sriwijaya Indralaya University, from May to July 2022. The study was prepared using a Randomized Group Design (RGD) with 4 treatments, each treatment was repeated 3 times and received 12 treatment units, each treatment unit had 3 plants, so that the total number of plants was 36 plants. P0= Control P1= 0.5 g NPK/polybag P2= 1 g NPK/polybag P3= 1.5 g NPK/polybag. Observed parameters include plant height, number of leaves, degree of leaf greenness, leaf area, fresh weight of the crown, fresh weight of the leaves, fresh weight of the roots, length of the roots, dry weight of the crown, dry weight of the leaves and dry weight of the roots. Based on the results of the study, it was shown that the administration of the recommended dose of NPK fertilizer P2 = 1 g NPK/Polybag gave the best results compared to other dose treatments.